To study the challenges in the implementation of “Foundation Course” of newly launch competency-based medical education curriculum among Indian medical colleges - Ramesh Pawar; Sunita Vagha; Varsha Pande; Sanjeev Chaudhary (Asian Journal of Medical Sciences, 2022)
Background: Medical knowledge is advancing at a rapid pace in a world, where technological evolution is at an all-time high. However, the health-care system falls well short of acceptable standards when it comes to meeting patient demands. Our medical environment, on the other hand, requires conscious revamping to increase healthcare quality. Traditional training approaches are significantly lacking in this era of value-based medicine, which prioritizes quality measurement and provider proficiency. Competency-based medical education (CBME), with its emphasis on individual, programmatic and institutional outcomes, has the ability to realign medical education with this social expectation. However, CBME implementation, on the other hand, is fraught with many challenges.